Ghana 'rising'?: A socioeconomic snapshot of Ghana's place in the 'Africa rising' narrative - Baker, Emma (Energy Research Centre, 2017)
The 'Africa Rising' narrative, which has gained popularity since the late 2000s, refers to the considerable economic and social gains that have been made across the continent since the start of the new millennium. Heralded as more than just GDP growth and poverty reduction, supporters of the 'Africa Rising' narrative also make reference to structural change, macroeconomic improvements and a growing middle class among sub-Saharan African countries. However, there are many who dispute these claims, arguing instead that recent economic growth has not been inclusive and sustainable, and many challenges still exist. This dissertation takes the case study of Ghana as a lens through which to explore the arguments in more detail and determine whether robust, reliable evidence exists to support the claims that Ghana is 'rising', both economically and socially. Using the headings of poverty, economic growth, and employment and equality, socioeconomic data collected from Ghana from the year 2000 onwards was analysed to assess the evidence behind the claims and counter-claims made. Despite significant data limitations, the findings present a mixed picture of Ghana's recent economic growth and development, with substantial progress made in poverty reduction, economic growth and income per capita, but considerable challenges remaining in terms of the current macroeconomic crisis, high youth unemployment and rising income inequality. Ghana's current development pathway, based primarily on commodities and oil revenues, is likely to be unsustainable in the long-term, and the slow rate of structural change, especially in manufacturing, means that growth so far has not been sufficiently inclusive or equitable to benefit the majority of the population. Within the broader context of the 'Africa Rising' narrative, the study also brought to light two important considerations: firstly, that significant data limitations exist within national statistics, making it necessary for claims to be investigated thoroughly; and secondly, that it is important to examine the case of individual countries such as Ghana before painting a whole continent with the same brush.